Financial Feasibility Analysis Of Red Chili Farming In Ketol Sub-District, Aceh Tengah Regency - Qhisthina Atikah; Safrika Safrika; Sukma Riani; Bagio Bagio; Akhmad Baihaqi (Politeknik Pertanian Negeri Samarinda, 2025)
Agriculture is the backbone of Indonesia's economy, absorbing labor and contributing significantly to national income. Optimization through technology and efficient resource management is essential to enhance farmer welfare and productivity. This study aims to analyze the financial feasibility of red chili farming in Ketol District, Central Aceh Regency, where farmers have shifted from sugarcane to chili due to economic, environmental, and social factors. The financial feasibility analysis includes: (1) income analysis, (2) R/C ratio, and (3) Break-Even Point (BEP). The results show that red chili productivity reaches 1,210 kg per planting season, with a selling price of Rp. 43,400/kg, generating an income of Rp. 39.8 million per season—higher than the national average. Financial analysis reveals an R/C ratio of 4.15, a production BEP of 291 kg (actual production: 1,210 kg), and a price BEP of Rp. 10,433/kg (selling price: Rp. 43,400/kg). These findings demonstrate the competitive advantage of red chili farming in the region, supported by high productivity and input efficiency. The study concludes that intensive technology-based red chili farming is economically viable and should be sustained through price stabilization strategies and market diversification